Pavement Deterioration Analysis for Rural Roads using HDM-4. Issue 1 (June 2021) - Anand, Sanchit; Gaur, Arun; Singh, Vaishnavi; Sharma, Abhinav
Abstract: Highway Development and Management (HDM-4) is comprised of decision-making tools used to assess the economic, social, and environmental viability of project development proposals to arrive at the best investment decisions. The entire system is built on various functions of pavement performing under numerous structural and environmental influences. The present work aims to study pavement distress and deteriorations prevailing on rural roads. At each stage, the road deterioration models predict impacts of distress at different rates and scenarios over each of the study sections. The analysis presents alternative maintenance and improvement strategies that could be implemented judiciously under scheduled or responsive routine assessments of road performance. Moreover, the analysis and output data for distress projection as obtained from HDM-4 is also validated from the existing pavement deterioration condition of the selected sections. The comparison of deterioration before and after works and the economic indicators delineated that Overlay for rural road sections is considered to be the most suitable alternative possible among others. Furthermore, the validation of the deterioration levels as predicted through HDM-4 indicates very low variation in the range of 2%-10% from the existing pavement deterioration levels. The results of this study are useful for developing pavement maintenance management strategies for rural roads network with similar characteristics.